Experimental analysis of dissolution reconstruction of deep dolomite reservoirs: A case study of the Cambrian dolomite reservoirs in the Tarim Basin - Zhang, Xin; Li, Bin; Peng, Jun; Qu, Fang; Zhang, Kun; Yang, Suju; Xu, Qingqi (Frontiers in Earth Science, 2022)
The deeply buried carbonate reservoir of Cambrian is an important target of oil and gas exploration in the Tarim Basin. Understanding the dissolution mechanism of the deep-buried carbonate reservoir is an urgent problem to be solved. In this study, 11 carbonate samples from three types of deep reservoirs in Tarim Basin were selected as experimental objects, and the dissolution process of carbonate reservoir was simulated by using an advanced reaction system of continuous flow at high temperature and high pressure. The dissolution test of continuous flow shows that the burial depth has an effect on carbonate dissolution, with the increasing of the depths from shallow to deep, the dissolution ability of acidic fluids in carbonate rocks increases first and then decreases. A comparison of dissolution results from different lithologic samples shows that the incomplete dolomitization calcite in the diagenetic stage provides the material basis for dissolution in the later stage. The relationship between reservoir type and physical property is discussed, and it is found that the permeability of the fracture-type and pore-fracture samples increase significantly after dissolution, indicating the pre-existing pores of carbonate rocks may be critical to the formation of high-quality reservoirs in deeply buried conditions. An interesting phenomenon was found by comparing the dissolution rates of experimental samples shows that the dissolution rate of dolomite reservoir has a trend of first increasing and then decreasing under the deeply buried environment, which proves that there is an optimal dissolution range of dolomite in the deeply buried environment, which is conducive to the formation of dolomite reservoir. The genetic model of burial dissolution in deep carbonate reservoirs was established and indicated that the search for dolostone reservoirs near the Himalayan fault may be a new idea for Cambrian deep oil and gas exploration.